2020
DOI: 10.12688/f1000research.24654.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a novel multiplex proteomics technology for detection of changes in serum protein concentrations that may correlate to tumor burden

Abstract: Background: To account for cancer heterogeneity, we previously introduced the concept of “personalized” tumor markers, which are biomarkers that are informative in subsets of patients or even a single patient. Recent developments in various multiplex protein technologies create excitement for the discovery of markers of tumor burden in individual patients, but the reliability of the technologies remains to be tested for this purpose. Here, we sought to explore the potential of a novel proteomics platform, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The micro-ELISA array technology from RayBiotech combines 25 non-overlapping glass-slide arrays to perform up to 1,000 miniature sandwich ELISAs simultaneously, targeting mostly inflammation-related proteins, including cytokines, chemokines, growth factors, tumor markers, and transcription factors (37)(38)(39)(40)(41)(42)(43). Each 75mm x 25mm glass slide contains 16 identical antibody Performance data by the manufacturer reports high precision with an average intra-assay CV of 7-10% and inter-assay CV of 10-15%, and a dynamic range of around 3-to 4-log concentration.…”
Section: Micro-elisa Arraymentioning
confidence: 99%
See 2 more Smart Citations
“…The micro-ELISA array technology from RayBiotech combines 25 non-overlapping glass-slide arrays to perform up to 1,000 miniature sandwich ELISAs simultaneously, targeting mostly inflammation-related proteins, including cytokines, chemokines, growth factors, tumor markers, and transcription factors (37)(38)(39)(40)(41)(42)(43). Each 75mm x 25mm glass slide contains 16 identical antibody Performance data by the manufacturer reports high precision with an average intra-assay CV of 7-10% and inter-assay CV of 10-15%, and a dynamic range of around 3-to 4-log concentration.…”
Section: Micro-elisa Arraymentioning
confidence: 99%
“…A latest study employed the micro-ELISA array from Raybiotech to identify new diagnostic biomarkers in ovarian cancer and validated nine candidates using ELISA (143). However, Ren et al reported incongruities between the micro-ELISA array and ELISA data for nine protein candidates in pancreatic cancer (41). The overall findings illustrated that inconsistencies in protein quantification between different ultrasensitive multiplex immunoassays are highly analyte dependent.…”
Section: Limitations and Technical Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation